Alberta [general map] - Alberta. Department of Lands and Mines (Office of the Surveyor General of Canada, 1948)
This is a general map of Alberta in 1948 showing highways (surfaced), roads (improved earth), First Nations reserves, parks, forest reserves and conservation areas, railways, cities and towns. Scale 1:2,217,600, or 35 miles to 1 inch. Relief shown by spot heights. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Shows highways (surfaced), roads (improved earth), First Nations reserves, parks, forest reserves and conservation areas, railways, cities and towns.